1966
DOI: 10.1016/0026-0495(66)90145-4
|View full text |Cite
|
Sign up to set email alerts
|

A diabetogenic polypeptide from bovine adenohypophysis similar to that excreted in lipoatrophic diabetes

Abstract: A polypeptide has been isolated from bovine adenohypopbysis which antagonizes the hypoglycemic effect of exogenous insulin and which, per se, induces loss of carbohydrate tolerance in men and dogs. Mild acid hydrolysis of the active polypeptide yields a compound which retains the same biological properties. Characteristics of the active principle and its hydrolytic product is the long duration of their activities, the greatest intensity of the effects TN RECENT COMMUNICATIONS being observed between 34 and 60 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, the diabetogenic activity of the bovine anterior pituitary is not necessarily the exclusive property of GH-related compounds. In 1966 a polypeptide was extracted and found to be diabetogenic in man and dogs (Louis et al, 1966). This material was named bovine diabetogenic peptide and possessed neither growth-promoting activity (Tutwiler & Louis, 1971) nor lactogenic activity (Louis & Conn, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…However, the diabetogenic activity of the bovine anterior pituitary is not necessarily the exclusive property of GH-related compounds. In 1966 a polypeptide was extracted and found to be diabetogenic in man and dogs (Louis et al, 1966). This material was named bovine diabetogenic peptide and possessed neither growth-promoting activity (Tutwiler & Louis, 1971) nor lactogenic activity (Louis & Conn, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Via abnormal neurohumoral signals a loss of fat in the subcutis and internal depots is induced concomitant with insulin resistance (1,21,24,29). How these signals act in detail is not known, but in both animal experiments and clinical studies, urinary peptides have been found with adipo- kinetic, diabetogenic and anti-insulin properties (7,20,21). In the diencephalic syndrome of emaciation a similar loss of subcutaneous fat occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is associated with hypothalamic dysfunction. It is thought that both abnormal humoral and neural stimuli may induce insulin resistance and loss of fat depots (1,6,7,20,21,22,24,26,29).…”
Section: Abstract: C-peptide Lipoatrophic Diabetes Urinary Polypepmentioning
confidence: 99%
“…Other possibilities for active peptide fragments that come to mind are one responsible for regulation of growth and another for stimulation of lactation. The relation of the anti-insulin peptide extracted from bovine pituitaries 48 to the growth hormone fragments should be explored.…”
Section: Etiological Factors In Human Diabetesmentioning
confidence: 99%